2017
DOI: 10.1042/cs20160618
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell–oligodendrocyte interactions in small vessel disease and aging

Abstract: Cerebral small vessel disease (SVD) is a prevalent, neurological disease that significantly increases the risk of stroke and dementia. The main pathological changes are vascular, in the form of lipohyalinosis and arteriosclerosis, and in the white matter (WM), in the form of WM lesions. Despite this, it is unclear to what extent the key cell types involved–the endothelial cells (ECs) of the vasculature and the oligodendrocytes of the WM–interact. Here, we describe the work that has so far been carried out sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 116 publications
0
43
0
1
Order By: Relevance
“…Furthermore, the Austrian Stroke Prevention Study found an association between intercellular adhesion molecule levels and WMH progression at 3 and 6 years (Markus et al 2005). Overall, these studies indicate that altered endothelial cell signaling might cause oligodendrocytes to be more vulnerable to damage, either by reducing their exposure to pro-survival factors or by reducing the ability of white matter to repair itself after injury (Rajani & Williams 2017 In summary, endothelial dysfunction is a pathological hallmark of SVD (Poggesi et al 2016). Immunohistological labeling shows evidence of vessel wall thickening and upregulation of hypoxia-related markers within white matter lesions (Fernando et al 2006).…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…Furthermore, the Austrian Stroke Prevention Study found an association between intercellular adhesion molecule levels and WMH progression at 3 and 6 years (Markus et al 2005). Overall, these studies indicate that altered endothelial cell signaling might cause oligodendrocytes to be more vulnerable to damage, either by reducing their exposure to pro-survival factors or by reducing the ability of white matter to repair itself after injury (Rajani & Williams 2017 In summary, endothelial dysfunction is a pathological hallmark of SVD (Poggesi et al 2016). Immunohistological labeling shows evidence of vessel wall thickening and upregulation of hypoxia-related markers within white matter lesions (Fernando et al 2006).…”
mentioning
confidence: 88%
“…Endothelial cells can also have a direct impact on oligodendrocytes, which are derived from oligodendrocyte precursor cells (OPC) (Rajani and Williams 2017). Oligodendrocyte precursor cells arise from many different regions of the brain during development and are also present throughout the adult brain.…”
Section: The Vascular Network and Cerebral White Mattermentioning
confidence: 99%
See 3 more Smart Citations